Estudo sobre o tratamento de água nas escolas estaduais e rurais do município de Abaetetuba - LIMA, Bárbara Pereira (2019)
The present work aims to investigate the existence of water treatment processes in rural and urban schools in the city of Abaetetuba. The methodology used to carry out this investigation was the interview of 08 employees in general, 04 of schools in the rural area and 04 in the urban area. The interview was made through a virtual questionnaire to know in fact how the water conditions consumed in schools are. This was built with the help of a computational tool, which left the creative form and easy access called Google Drive. The analysis of the virtual questionnaire applied to the interviewees was based on their reports, which revealed that the institutions do not care and do not actually worry about the state of the water ingested in the school environment, although both make use of a simple method of such as chemical filters and disinfectants.